Quantifying the Availability of Vertebrate Hosts to Ticks: A Camera-Trapping Approach - Hofmeester, Tim R.; Rowcliffe, J. Marcus; Jansen, Patrick A. (Frontiers in Veterinary Science, 2017)
The availability of vertebrate hosts is a major determinant of the occurrence of ticks and tick-borne zoonoses in natural and anthropogenic ecosystems, and thus drives disease risk for wildlife, livestock and humans. However, it remains challenging to quantify the availability of vertebrate hosts in field settings, particularly for medium-sized to large-bodied mammals. Here, we present a method that uses camera traps to quantify the availability of warm-bodied vertebrates to ticks. The approach is to deploy camera traps at questing height at a representative sample of random points across the study area, measure the average photographic capture rate for vertebrate species, and then correct these rates for the effective detection distance. The resulting ‘passage rate’ is a standardized measure of the frequency at which vertebrates approach questing ticks, which we show is proportional to contact rate. A field test across twenty 1-ha forest plots in the Netherlands indicated that this method effectively captures differences in wildlife assemblage composition between sites. Also, the relative abundances of three life stages of the sheep tick Ixodes ricinus from drag sampling were correlated with passage rates of deer, which agrees with the known association with this group of host species, suggesting that passage rate effectively reflects the availability of medium- to large-sized hosts to ticks. This method will facilitate quantitative studies of the relationship between densities of questing ticks and the availability of different vertebrate species – wild as well as domesticated species – in natural and anthropogenic settings.